2015
DOI: 10.1523/jneurosci.3031-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact Prediction by Looming Visual Stimuli Enhances Tactile Detection

Abstract: From an ecological point of view, approaching objects are potentially more harmful than receding objects. A predator, a dominant conspecific, or a mere branch coming up at high speed can all be dangerous if one does not detect them and produce the appropriate escape behavior fast enough. And indeed, looming stimuli trigger stereotyped defensive responses in both monkeys and human infants. However, while the heteromodal somatosensory consequences of visual looming stimuli can be fully predicted by their spatiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 65 publications
8
64
0
Order By: Relevance
“…The attention capture explanation is also supported by the RTs recorded in response to tactile stimulation delivered during the reach-to-grasp movement execution in a laboratory setting: RTs in the postmovement period, once the grasp of the goal object has taken place, are faster than during the execution period . Furthermore, it has recently been suggested that the enhancement effect of the visual looming stimuli on tactile events stems from a defensive mechanism, that is, we inherently perceive approaching objects as more dangerous, as compared to objects leaving our personal space (Clery, Guipponi, Odouard, Wardak, & Ben Hamed, 2015;Kandula, Hofman, & Dijkerman, 2015). Importantly, the attention-capture-like effect found in this study also supports the multisensory thesis concerning looming stimuli (Cappe, Thut, Romei, & Murray, 2009), since the ball arrival carries not only visual information, but also auditory information.…”
Section: Discussionsupporting
confidence: 74%
“…The attention capture explanation is also supported by the RTs recorded in response to tactile stimulation delivered during the reach-to-grasp movement execution in a laboratory setting: RTs in the postmovement period, once the grasp of the goal object has taken place, are faster than during the execution period . Furthermore, it has recently been suggested that the enhancement effect of the visual looming stimuli on tactile events stems from a defensive mechanism, that is, we inherently perceive approaching objects as more dangerous, as compared to objects leaving our personal space (Clery, Guipponi, Odouard, Wardak, & Ben Hamed, 2015;Kandula, Hofman, & Dijkerman, 2015). Importantly, the attention-capture-like effect found in this study also supports the multisensory thesis concerning looming stimuli (Cappe, Thut, Romei, & Murray, 2009), since the ball arrival carries not only visual information, but also auditory information.…”
Section: Discussionsupporting
confidence: 74%
“…More precisely, the PPS constraint specifies that body signals occur within the limited space surrounding the body—the PPS—and hence for signals to bind with body‐related information they must occur within this space. In this line, recent work has depicted a more complete picture regarding the encoding and functional role of the PPS, and has revealed the stochastic and predictive nature of this particular form of spatial representation critical for bodily self‐consciousness. Thus, we propose that by highlighting the stochastic or statistical inference nature of PPS representation, as one fundamental component of bodily self‐consciousness, it may be possible to leverage recent advances in computational models dedicated to multisensory integration in the study of bodily self‐consciousness.…”
Section: Bodily Self‐consciousnessmentioning
confidence: 99%
“…The visual looming effect is purported to activate fast intercortical connections and increase sensorimotor function 32 and may even lead to an increase in cognitive function. Such effects, if present, could mask immediate negative effects from RHI.…”
Section: Immediate Improvementsmentioning
confidence: 99%